Volume rendering in scientific applications - Krömker, Susanne; Rings, Jörg (Reactive flows, diffusion and transport, 2007)
The increasing amount of 3D data in measurements and simulations needs a tool to visualize the interior in a convenient way. This can be done with so-called volume rendering techniques that allow for treating voxel-based data by assigning appropriate opacities to it.
Gesehen am 13.06.2018